Enhancing the performances of recycling folded cascode OpAmp in nanoscale CMOS through voltage supply doubling and design for reliability. (22nd November 2012) - Mak, Pui‐In; Liu, Miao; Zhao, Yaohua; Martins, Rui P.
ABSTRACT Current‐oriented operational amplifier (OpAmp) design has been common for its orderly current‐to‐speed tradeoff. However, for high‐precision or high‐linearity applications, increasing the current does not help much, as the supply voltage (VDD) and intrinsic gain of the MOSFETs in ultra‐scaled CMOS technologies are very limited. This paper introduces voltage‐oriented circuit techniques to address such limitations. Specifically, a 2xVDD‐enabled recycling folded cascade (RFC) OpAmp is proposed. It features: (1) current recycling to enhance the effective trans conductance by 4x with no extra power; (2) transistor stacking to boost the output resistance by one to two orders of magnitude; and (3) VDD elevating to enlarge the linear output swing by 4x. Comparing with its 1xVDD RFC and FC counterparts, the proposed solution achieves 20‐dB higher DC gain (i.e. 72.8 dB) in open loop and 20‐dB lower IM3 (i.e., –76.5 dB) in closed loop, under the same power budget of 0.6 mW in a 1‐V General Purpose 65‐nm CMOS process. In many applications, these joint improvements in a single stage are already adequate, being more power efficient (i.e. less current paths), stable (i.e. more phase margin), and compact (i.e. no frequency compensation) than multi‐stage OpAmps. Voltage‐conscious biasing and node‐voltage trajectory check ensure the device reliability in both transient and steady states. No specialized high‐voltage device is necessary. Copyright © 2012 John Wiley & Sons, Ltd.